Volatility Timing in the Vietnamese Stock Market - Nguyen, Thi Hoang Anh (Journal of International Economics and Management, 2016)
In this paper, we evaluate the economic value that arise from incorporating conditional volatility when forecasting the covariance matrix of returns for both short and long horizons in the Vietnamese stock market, using the volatility timing framework of Fleming et al. (2001). We report three main findings. First, investors are willing to pay to switch from the static to a dynamic volatility timing strategy. Second, there is negligible difference in forecast performance among short and memory volatility models. However, the more parsimonious EWMA family models tend to produce better forecasts of the covariance matrix than those produced by the GARCH family volatility models at all investment horizons. Third, when transaction costs are taken into account, the gains from daily rebalanced dynamic portfolios deteriorate. However, it is still worth implementing the dynamic strategies at lower rebalancing frequencies. Our results are robust to estimation error in expected returns, the choice of risk aversion coefficient and estimation windows.